Membangun Pemerintahan Kolaboratif melalui Literasi Digital di Kalangan ASN dan Masyarakat - Zein, M Harry Mulya (Universitas Pahlawan Tuanku Tambusai, 2024)
The use of digital literacy in governance has become one of the important factors in improving collaboration between the government and the community. This research aims to improve digital literacy among civil servants and the community in Pasir Gunung Selatan Urban Village, Cimanggis District, Depok City, with a focus on the four pillars of digital literacy: digital skills, digital security, digital culture, and digital ethics. The method used in this research is the descriptive qualitative method through socialization, mentoring, and evaluation of increased understanding of digital literacy. The results showed an increase in understanding and awareness among State Civil Apparatus and the community regarding the importance of digital literacy in supporting collaborative governance. With the improvement of digital literacy, it is expected that there will be better synergy between the government and the community in terms of effective and transparent governance. Keywords: Digital Literacy, Collaborative Government, Community